Philipp Melanchthons Beziehungen zu Ungarn und Siebenbürgen im Spiegel von Netzwerken und Korrespondenzen - Mundhenk, Christine (Journal of Early Modern Christianity, 2021)
For decades, Melanchthon maintained intensive relationships with Hungary. Students from there formed the largest group of foreign students at Wittenberg University. Melanchthon supported them during their studies and kept in touch with some of them after they returned to their home country. Networks were necessary, so that letters and messages reached their recipients. By writing letters of recommendation to others, Melanchthon enabled his students to establish contacts and to build up their own network. At the Coetus Hungaricus existing at Wittenberg University the Hungarian students also made contacts, which were useful to them later. Edited correspondences allow to track down and describe such interlinking. A network of contacts in Hungary can be depicted between Johannes Honterus, Valentin Wagner, Georg Werner, Sigismund Tordai-Gelous, Mátyás Dévai Bíró and Gáspár Heltai. The relations between them as well as the close contact with Melanchthon provided mutual assurance and helped to control the doctrine adopted from Wittenberg.